1998
DOI: 10.1002/(sici)1097-0142(19980715)83:2<360::aid-cncr21>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Loss of material from chromosome arm 1p during malignant progression of meningioma revealed by fluorescent in Situ hybridization

Abstract: BACKGROUND Atypical and anaplastic meningiomas tend to recur and to invade adjacent brain, bone, and skin. They also can metastasize to extracranial organs such as the lung, liver, or bone, causing death. Recent reports have indicated that allelic deletion of chromosome 1p is associated with malignant progression of meningiomas. METHODS Cytogenetic analysis of 37 meningiomas was performed using double‐target fluorescent in situ hybridization (FISH) and focusing on chromosome arm 1p. The meningioma series inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 18 publications
(31 reference statements)
3
39
0
1
Order By: Relevance
“…8,34 Several studies have succeeded in narrowing down the critical regions on 1p that relate to tumorigenesis of meningiomas. [12][13][14]35,36 Several candidate genes on 1p have been discussed with regard to their relationship with meningioma tumorigenesis or progression, including TP73, CDKN2C (encoding p18 INK4c ), RAD54L and ALPL. [37][38][39][40] The roles of these genes, however, are still controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,34 Several studies have succeeded in narrowing down the critical regions on 1p that relate to tumorigenesis of meningiomas. [12][13][14]35,36 Several candidate genes on 1p have been discussed with regard to their relationship with meningioma tumorigenesis or progression, including TP73, CDKN2C (encoding p18 INK4c ), RAD54L and ALPL. [37][38][39][40] The roles of these genes, however, are still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] We finally defined a candidate common LOH region which might associate with meningioma. This region, located at 1p36.11, was considerably narrowed down when compared with a 19.3-Mbp candidate locus, R2, located at 1p36.21-p34.1 by Buckley et al 16 Genes located at this region are shown in Supplemental Table S3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of a sex Table 2 Correlation Between the Numerical Abnormalities Observed for Chromosomes 1,9,10,11,14,15,17,22 chromosome in somatic cells is a relatively frequent agerelated phenomenon, usually including loss of the Y chromosome in bone marrow cells from older male individuals (40). However, it was never found at the high frequencies reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of heterozygosity (LOH) for chromosome 1p is frequently observed in a variety of tumors. These include neuroblastomas (Ariyama et al, 1995;Cheng et al, 1995;White et al, 1997), meningiomas (Ishino et al, 1998), pheochromocytomas, medullary thyroid carcinomas and neuroendocrine carcinoma (Moley et al, 1992), T cell acute lymphoblastic leukemia (Iolascon et al, 1997), colorectal carcinoma (Bomme et al, 1998;Di Vinci et al, 1998;Praml et al, 1995), mesothelioma (Lee et al, 1996), hepatoma (Chen et al, 1996), endometrial carcinoma (Arlt et al, 1996) and breast carcinomas (Borg et al, 1992;Munn et al, 1995;Nagai et al, 1995;Tsukamoto et al, 1998). A unique category of germ cell tumors, childhood endodermal sinus tumors involving the testis and extragonadal region in children less than 4 years of age, show recurrent cytogenetic abnormalities including deletion of distal 1p region (Perlman et al, 1996).…”
Section: Introductionmentioning
confidence: 99%